Africa uncorked : travels in extreme wine territory - Platter, John.; Platter, Erica (Cape Town : Double Storey Books, 2002)
A blend of travel diary and wine guide, it tells a series of stories - the brilliant wine and food discoveries made, the extraordinary historical sites stumbled across, the fascinating characters met.
North Africa: Morocco; Algeria; Tunisia; Egypt. East Africa: Ethiopia; Kenya; Tanzania. The islands: Madagascar; Reunion; Mauritius. Southern Africa: Zimbabwe; Namibia; South Africa. The End?. Wine notes; wine-speak.
Includes index.
Keywords: Wine and wine making -- Africa